Cyclovirobuxinum D suppresses lipopolysaccharide-induced inflammatory responses in murine macrophages in vitro by blocking JAK-STAT signaling pathway - Guo Dan; Li Jing-rong; Wang Ying; Lei Lin-sheng; Yu Chuan-lin; Chen Na-na (Acta Pharmacologica Sinica, 2016)
Dan GUO1, Jing-rong LI2, Ying WANG3, Lin-sheng LEI2, Chuan-lin YU2, Na-na CHEN2, * 1Nanfang Hospital, Southern Medical University, Guangzhou 510515, China; 2School of Pharmaceutical Sciences, Southern Medical University, Guangzhou 510515, China; 3China National Center for Biotechnology Development, Beijing 100039, China Aim: Cyclovirobuxinum D (CVB-D), an alkaloid isolated from the Chinese medicinal plant Buxus microphylla, has been found to be effective to treat cardiac insufficiency, arrhythmias and coronary heart disease. In the present study, we investigated the effects of CVB-D on the inflammatory responses in lipopolysaccharide (LPS)-stimulated murine macrophages in vitro and the underlying mechanisms. Methods: Murine macrophage cell line RAW264.7 cells were incubated in the presence of LPS (0.1 μg/mL) for 24 h. The cell viability was measured using MTT assay. The release of NO and cytokines were detected using the Griess test and ELISA, respectively. The mRNA and protein levels were determined using RT-PCR and Western blot, respectively. Reporter gene assays were used to analyze the transcriptional activity of NF-κB. Results: Treatment of RAW264.7 cells with CVB-D (25–300 μmol/L) did not affect the cell viability. Pretreatment with CVB-D (50, 100 and 200 μmol/L) concentration-dependently decreased NO release and iNOS expression in LPS-treated RAW264.7 cells (its IC50 value in inhibition of NO production was 144 μmol/L). CVB-D also concentration-dependently inhibited the secretion and mRNA expression of IL-1β and IL-6 in LPS-treated RAW264.7 cells. Furthermore, CVB-D remarkably inhibited the phosphorylation of STAT1 and STAT3, as well as JAK2 in LPS-treated RAW264.7 cells, but did not affect the activation of NF-κB and MAPKs pathways. Pretreatment with the JAK2 specific inhibitor AG490 (30 μmol/L) produced similar effects on NO release and iNOS expression in LPS-treated RAW264.7 cells. Conclusion: CVB-D exerts anti-inflammatory effects in LPS-stimulated murine macrophages in vitro at least in part by blocking the JAK-STAT signaling pathway. The anti-inflammatory actions of CVB-D may contribute to its cardioprotection. Keywords: cyclovirobuxinum D; macrophage; inflammation; nitric oxide; cytokine; JAK; STAT; myocardial infarction; cardioprotection This study is supported by grants from the Guangdong Natural Science Foundation (No S2011010003787, S2012010009056), Science and Technology Planning Project of Guangdong Province (No 2011B031800128), Science and Technology Bureau of Guangzhou (No 2011J4100085), and Science and Technology Bureau of Baiyun District of Guangzhou (No 2011-KZ-60). * To whom correspondence should be addressed. E-mail gdcnn_2011@126.com Received 2013-11-20 Accepted 2014-02-20